Waist-to-Height Ratio Is Independently Related to Whole and Central Body Fat, Regardless of the Waist Circumference Measurement Protocol, in Non-Alcoholic Fatty Liver Disease Patients - Pimenta, NM (2019)
BACKGROUND: Waist-to-height ratio (WHtR) has been reported as a preferable risk related body fat (BF) marker, although no standardised waist circumference measurement protocol (WCmp) has been proposed. The present study aimed to investigate whether the use of a different WCmp affects the strength of relationship between WHtR and both whole and central BF in non-alcoholic fatty liver disease (NAFLD) patients. METHODS: BF was assessed with dual energy X-ray absorptiometry (DXA) in 28 NAFLD patients [19 males, mean (SD) 51 (13) years and nine females, 47 (13) years]. All subjects also underwent anthropometric evaluation including height and waist circumference (WC) measurement using four different WCmp (WC1, minimal waist; WC2, iliac crest; WC3, mid-distance between iliac crest and lowest rib; WC4, at the umbilicus) and WHtR was calculated using each WC measurements (WHtR1, WHtR2, WHtR3 and WHtR4, respectively). Partial correlations were conducted to assess the relation of WHtR and DXA assessed BF. RESULTS: All WHtR were particularly correlated with central BF, including abdominal BF (r = 0.80, r = 0.84, r = 0.84 and r = 0.78, respectively, for WHtR1, WHtR2, WHtR3 and WHtR4) and central abdominal BF (r = 0.72, r = 0.77, r = 0.76 and r = 0.71, respectively, for WHtR1, WHtR2, WHtR3 and WHtR4), after controlling for age, sex and body mass index. There were no differences between the correlation coefficients obtained between all studied WHtR and each whole and central BF variable. CONCLUSIONS: Waist-to-height ratio was found a suitable BF marker in the present sample of NAFLD patients and the strength of the relationship between WHtR and both whole and central BF was not altered by using different WCmp in the present sample of NAFLD patients.